2015
DOI: 10.1007/s11356-015-5466-7
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater infiltration and surface runoff pollution reduction performance of permeable pavement layers

Abstract: In this paper, the laboratory-scale permeable pavement layers, including a surface permeable brick layer, coarse sand bedding layers (thicknesses = 2, 3.5, and 5 cm), and single-graded gravel sub-base layers (thicknesses = 15, 20, 25, and 30 cm), were built to evaluate stormwater infiltration and surface runoff pollution reduction performance. And, the infiltration rate (I) and concentrations of suspended solids (SS), total phosphorus (TP), chemical oxygen demand (COD), ammonia nitrogen, and total nitrogen (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The ceramic permeable brick had the best filtering effect on SS of the three bricks, and research has found that the physical interception of the surface layer inside the permeable brick played a major role in the removal of SS [2,18], which were mainly filtered by the voids and pores inside the permeable bricks, and the chord size distribution that can be used to characterize the size of the voids and pores was further researched [28]. The chord size was used to represent the size of the pores, and the chord length frequency was used to represent the number of pores.…”
Section: Results Of the Dynamic Filtration Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ceramic permeable brick had the best filtering effect on SS of the three bricks, and research has found that the physical interception of the surface layer inside the permeable brick played a major role in the removal of SS [2,18], which were mainly filtered by the voids and pores inside the permeable bricks, and the chord size distribution that can be used to characterize the size of the voids and pores was further researched [28]. The chord size was used to represent the size of the pores, and the chord length frequency was used to represent the number of pores.…”
Section: Results Of the Dynamic Filtration Experimentsmentioning
confidence: 99%
“…(f, g, h). The heavy metals were usually removed along with the filtering of the SS by the permeable bricks [2,14,15,18,31,32]; therefore, the removal rates of Zn, Cu and Pb were also relatively high. Due to the different binding abilities between the heavy metals and particles in the runoff, the removal rates of Zn, Cu and Pb by several packing systems were inconsistent [33].…”
Section: Results Of the Dynamic Filtration Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For permeability and reduction of runoff, installation of rain barrels, permeable pavement, and rain gardens are common effective options (Niu, Lv, Zhang, & Cui, 2016). Other yard renovations include infiltration beds, cisterns, and weeping tiles, all of which help to increase permeability and hold water on the property for slow release (Zimmer, Heathcote, Whiteley, & Schroeter, 2007).…”
Section: Case Studymentioning
confidence: 99%